Determination of diethylstilbestrol, zeranol and trenbolone in chicken meat of national and imported origin - Peña-Torres, Edgar Fernando; Benítez-Hernández, Asahel; García-Barrón, Sergio Erick; Peña-Morán, Omar Aristeo; Montero-Lara, Gabriel Ángel (Ecosistemas y Recursos Agropecuarios, 2023)
The present study analyzed the levels of Diethylstilbestrol (DES), zeranol and trenbolone acetate with immunoenzymatically assay in local and imported chicken breast samples. 72 samples of chicken breast of local and imported origin were used, zeranol and trenbolone was detected in the samples of local and imported meat; the hormone DES was not detected in any samples analyzed. Zeranol concentrations for local and imported were below to the Mexican regulations, furthermore, they did not show statistical differences between them. The presence of trenbolone acetate was found to be below the limits allowed by the Mexican regulations. The results suggest that it is necessary a continuously regulation of poultry production due to an excessive use of these compounds can be risky for the health of the consumer.